Magnesium Isotopes Archive the Initial Carbonate Abundances of Metasedimentary Rocks Prior to Thermal Decarbonation - Qingshang Shi; Yongsheng He; Zhidan Zhao; Franco Rolfo; Chiara Groppo; Nigel Harris; Hongjie Wu; Ningyuan Qi; Shan Ke (Geophysical Research Letters)
Abstract Investigating the carbonate preservation efficiency (CPE) of continental crust is crucial to understand the global carbon cycle, which requires constraints on initial carbonate abundances (ICAs) of crustal rocks. To link Mg isotopes to ICAs, we present elemental and Mg isotopic data for Himalayan carbonate‐bearing and carbonate‐free metasedimentary rocks. Given no evident melt extraction or external‐fluid infiltration, ICAs of these samples can be independently estimated by elemental data. Despite different carbonate species in the protoliths, all the samples show congruent relationship between their δ26Mg and ICAs, owing to the elevated carbonate δ26Mg and Mg/Ca in protoliths of calcite‐rich samples resulting from diagenetic processes. When collated with literature data, we suggest the observed correlation here can be applied to most carbonate‐bearing (meta‐)sedimentary rocks. Based on a steady state box‐model, we constrained the modern net carbonate accretion flux (9.50−5.56+9.50 Tmol/year) and the average time‐integrated CPE (∼80−43+20%) for continental crust.